Mountain plant communities: Uncertain sentinels?. (August 2019) - Malanson, George P; Resler, Lynn M; Butler, David R; Fagre, Daniel B
Mountain plant communities are thought to be sensitive to climate change and, thus, able to reveal its effects sooner than others. The status as sentinels of two plant communities are reviewed. Alpine treeline ecotones and alpine vegetation have been observed to respond to climate change in recent decades. The treeline has moved upslope and alpine communities have had some species increase and others decrease. The response for both, however, has been inconsistent if taken as a whole. Problematic factors for this response are outlined for both: abiotic and biotic interactions partially decouple the plant communities from climate. Differences across spatial and temporal scales complicate interpretation. Partial decoupling leads to nonlinear responses and difficulties for prediction and for planning mitigation.